A longitudinal study on sensitivity to symmetry in writing and associations with early literacy abilities - Yin, Li; McBride, Catherine (Frontiers in Education, 2023)
Young children reportedly find symmetrical prints, such as H, easier to copy and produce from memory than asymmetrical ones. Little is known about how sensitivity to symmetry in print relates to early word reading and writing development. We examined this in Chinese, a visually complex writing system featuring symmetrical patterns, such as or . Sixty preschoolers in Beijing completed a character decision task (experiment 1, Mage = 62.16 months) and a character learning task (experiment 2, Mage = 63.96 months), using stimuli matched on visual complexity and frequency but differing in symmetry, and were assessed on Chinese word reading and word writing abilities twice with a 2-year interval. Results show that children were significantly more likely to endorse symmetrical complex stimuli as possible Chinese than asymmetrical complex ones, and they learned to read symmetrical characters significantly better than asymmetrical ones, reflecting their sensitivity to symmetry in Chinese characters. However, with age and nonverbal IQ statistically controlled, sensitivity to symmetry was not uniquely associated with Chinese word reading or word writing abilities at any time; rather, asymmetrical character learning, which necessitates reduced sensitivity to symmetry, was uniquely associated with Chinese word writing concurrently and longitudinally. Findings highlight the close relationship between analytic perception of written words and early writing ability. (207 words)